VARIASI KUE TRADISIONAL DENGAN BAHAN DASAR SINGKONG DI DAPUR PASTRY HOTEL éL ROYALE BANDUNG - Binur P Napitupulu; Sri Dewiani (Akademi Pariwisata Darma Agung, 2020)
Pastry is a place to process, provide and serve the cake, bread, traditional cake, which neededby the guest. The guest in hotel can enjoy the cake which had made by the pastry section when the events need snack or dessert. Many types of cake served in hotel most produced which use modern cake recipi. Although indonesia is rich with many traditional cake which is not less in terms of taste and appearance of serve. So the authors doing research to know the variation types of traditional cake made of cassava at el royal hotel bandung and for know development effort of traditional cake made from cassava at el royale hotel bandung, and do experiment. This research doing in two places are : el royale hotel bandung and laboratory of pastry at tourism hotel academy darma agung medan. The selection of place at el royale hotel bandung is to get information about the traditional cake in hotel , which doing by interviuw with 7 pastry staffs. To develop variation of cake the author doing experiment at pastry laboratory at tourism hotel academic darma agung medan, the result of experiment was evaluated by lecture, staff and student with total 43 persons as sample from 245 population. From the result of research the author take conclusion cassava layer cake, cheese bolu tape, and getuk. From the result of experiment which had made the colour, taste and texture are very interesting, so from this processed product is very good to reccomended at the pastry in el royale hotel bandung.